Hypoxia exposure and B‐type natriuretic peptide release from Langendorff heart of rats. (26th August 2016) - Anttila, K.; Streng, T.; Pispa, J.; Vainio, M.; Nikinmaa, M.
Abstract: Aim: We studied whether available oxygen without induced mechanical stretch regulates the release of the biologically active B‐type natriuretic peptide (BNP) from Langendorff heart. Methods: Rat hearts were isolated and perfused with a physiological Krebs–Henseleit solution at a constant hydrostatic pressure in Langendorff set‐up. The basal O2 level of perfusate (24.4 ± 0.04 mg L −1 ) was gradually lowered to 3.0 ± 0.01 mg L −1 over 20 min using N2 gas ( n = 7). BNP and O2 level were measured from coronary flow. During control perfusions ( n = 5), the O2 concentration was kept at 26.6 ± 0.3 mg L −1 . Results: A low oxygen concentration in the perfusate was associated with a significant increase in BNP release ( F = 40.4, P < 0.001). Heart rate decreased when the oxygen concentration in the perfusate reached 9.1 ± 0.02 mg L −1 and continued to fall in lower oxygen concentrations ( F = 14.8, P < 0.001). There was also a significant but inverse correlation between BNP and oxygen in the coronary flow ( R 2 = 0.27, P < 0.001). Conclusion: In the spontaneously beating Langendorff rat heart, a decreasing concentration of oxygen in the ingoing perfusion increased the secretion of BNP. The effect of oxygen was independent of mechanical stretch of the heart as it occurred even when the heart rate decreased but the pressure conditions remained constant. The difference in the oxygen capacitance of blood and Krebs–Henseleit solution appears to be a major factor affecting secretion of BNP, which is correlated with the oxygen tension of myocardial cells and affected both by the oxygen concentration and capacitance of solution perfusing the heart and by the coronary flow.